Chédiak-Higashi syndrome: presentation of seven cases - Carnide, Eugénia Maria Grilo; Jacob, Cristina Miuki Abe; Pastorino, Antonio Carlos; Bellinati-Pires, Raquel; Costa, Maria Beatriz Guimarães; Grumach, Anete SevciovicGrumach (São Paulo Medical Journal, 1998)
CONTEXT: Chédiak-Higashi Syndrome (CHS) is a rare autosomal recessive disease characterized by recurrent infections, giant cytoplasmic granules, and oculocutaneous albinism. OBJECTIVE: To describe clinical and laboratory findings from CHS patients. DESIGN: Case report. SETTING: The patients were admitted into the Allergy and Immunology Unit of the Instituto da Criança, a tertiary public care institution. CASES REPORT: Seven patients had oculocutaneous albinism, recurrent infections and giant cytoplasmic granules in the leukocytes. One patient had low IgG levels and three showed impaired bactericidal activity of neutrophils. Six patients died of infectious complications during the accelerated phase. Therapy included ascorbic acid and antibiotics. Chemotherapy was used for the accelerated phase in two patients. Bone marrow transplantation (BMT) was proposed for one patient. DISCUSSION: The authors emphasize the need for early diagnosis and therapy of CHS. BMT should be indicated before the accelerated phase of the disease has developed.